Dynamics of the Peasant Territories in Alagoas: The articulation of families settled to expand Agroecology in agrarian reform areas - Santana,José Ubiratan Rezende (2022)
Abstract This article analyzes the process of expanding Agroecology in agrarian reform territories and the nuances of access to the land by peasant families in rural settlements. Agrarian reform settlements are constituted from the organization of peasant families, in their historical struggle for access to the land and regularization of their territories. This change in the land use and tenure regime has meant an increase in the amount and diversity of food produced in these agroecosystems, especially where there are substantiated experiences in Agroecology, which is considered a Science in the field of complexity, used as a reference by the peasant movements to guide the production of healthy and local food, particularly those linked to the traditional and peasant cultures. The study involved two settlements in the state of Alagoas, Flor do Bosque and Dom Helder Câmara, located in the municipalities of Messias and Murici, respectively. The data analyzed were obtained from the diagnosis conducted by the Radis system and from field diary records. The results indicated that the families involved in organic and agroecological production are responsible for an increase in productive diversity, with food produced exclusively by them, with 48% for Flor do Bosque and 39% for Dom Helder Câmara. It was identified, in both settlements, the presence of families without legal ownership of the land, but that produce agroecologically and organically. This fact acquires great relevance, since this directly implies the development of the territorialization of the peasantry in these settlements.